Radiographic and Clinical Results of Combined Bone and Soft-Tissue Tailored Surgeries for Hip Dislocation and Subluxation in Cerebral Palsy - Giulia Beltrame; Artemisia Panou; Andrea Peccati; Haridimos Tsibidakis; Francesco Pelillo; Nicola Marcello Portinaro (Children)
Background/Objectives: The aim of the study is to present middle-term results of tailored bone and soft-tissue surgeries in subluxated and dislocated hips in children affected by cerebral palsy. Methods: A total of 87 medical records belonging to 73 children affected by CP, treated with combined soft-tissue releases, VDO, and pelvic osteotomy, were reviewed retrospectively. Radiological measurements of AI, RI, and NSA were obtained before surgery, postoperatively, at 12 and 24 months after surgery. Results were assessed globally and by GMFCS, age, and Robin score. Results: Postoperative results are not statistically influenced by age and GMFCS levels at surgery. All three radiographic parameters showed persistent statistically significant improvement after surgery and at follow-up, respectively. Conclusions: Obtaining the best possible concentric reduction of the femoral head in the acetabulum, with simultaneous multilevel soft-tissue rebalancing, creates the best mechanical and biological environment to allow the reshaping of both articular surfaces, obtaining physiological internal joint pressure. The anatomical best congruency is protective from recurrence.